Using NIMBY rhetoric as a political resource to negotiate responses to local energy infrastructure: a power line case study - Batel, S.; Devine-Wright, P. (Local Environment, 2020)
Research has shown how the NIMBY explanation for local opposition to energy infrastructures has made its way into the discourses of developers, policy makers, the media and active protesters. However, few studies have explored how community members draw on discourses of NIMBYism to interpret and negotiate responses to local energy proposals. We address this gap drawing on qualitative data from two UK case studies. Analyses show that NIMBY, as a representation of objection, is both widespread and polysemic. Aside from providing a means to talk about space, NIMBY is sometimes rejected by discourses positioning publics as custodians of valued landscapes. In other instances, it is assumed to be a normative and legitimate way for participants to decide what is best for them in a neo-liberal society. The findings reinforce the importance of examining socio-cultural dimensions of social acceptance, specifically representations of community responses to infrastructures as political devices in local siting disputes, and publics as reflexive actors.